PERAN PENTING MENINGKATKAN PERKEMBANGAN UNTUK ANAK DISABILITAS DI SLB CENDANA RUMBAI - Nurshal, Rezki Amalia; Asriani, Dwi Suci; Mutiara, Sherly (LPPM Universitas Awal Bros, 2024)
Children with disabilities have the potential to grow optimally when supported with appropriate stimulation and care. This community service activity aimed to enhance the understanding of teachers and parents at SLB Cendana Rumbai regarding their crucial role in supporting the development of children with disabilities. The methods included interactive counseling sessions, training on developmental stimulation strategies, and experience-sharing discussions. The results showed improved awareness among participants about appropriate approaches in guiding children with disabilities, along with increased motivation to engage actively in their developmental process. This initiative is expected to be a starting point in creating a more inclusive and supportive educational environment.